Comprehensive Evaluation of Endocytosis-Associated Protein SCAMP3 in Hepatocellular Carcinoma - Zhou A; Liu H; Tang B (Dove Medical Press, 2020)
Ao Zhou,1 Hongjing Liu,2 Bin Tang1,3 1Basic Medical College, Southwest Medical University, Luzhou 646100, People’s Republic of China; 2The Affiliated Hospital of Southwest Medical University, Southwest Medical University, Luzhou 646100, People’s Republic of China; 3Key Laboratory of Process Analysis and Control of Sichuan Universities, Yibin University, Yibin 644000, People’s Republic of ChinaCorrespondence: Bin TangBasic Medical College, Southwest Medical University, Luzhou 646100, People’s Republic of ChinaEmail tangbin8888@163.comBackground: Secretory carrier membrane proteins 3 (SCAMP3) is an endocytosis-associated protein involved in regulating endosomal pathways and the trafficking of vital signaling receptors. This study aimed to comprehensively assess the role of SCAMP3 in hepatocellular carcinoma (HCC) by integrated bioinformatics analysis.Methods: In this study, bioinformatics databases were used to explore the differential expression status and prognostic value of SCAMP3 gene in HCC, and bioinformatics analyses of survival data and interactors of SCAMP3 were conducted to predict the prognostic value of SCAMP3 in HCC.Results: Using the TCGA data, our data shows that SCAMP3 mRNA expression is most significantly different between liver and hepatocellular carcinoma tissues and higher expression of SCAMP3 has unfavorable prognostic significance in HCC. Tumor grade, stage, and gender also showed a significant relevance with SCAMP3 expression. High SCAMP3 expression of males revealed significantly poorer survival and progression compared with low SCAMP3 expression of males. BioGRID statistics explores 79 unique interactions with SCAMP3 and multiple post translational modifications. Further analysis finds that SOCS2 may negatively correlate with SCAMP3, while GBA, MX1, and DDOST positively correlate with SCAMP3. Moreover, ncRNA analysis shows that SCAMP3 gene expression is positively associated with lncRNA SBF2-AS1 and negatively related with Has-miR-145. The expressions of SBF2-AS1 and Has-miR-145 are also significantly related with survival in HCC.Discussion: SCAMP3 expression can be affected by multiple genes or ncRNAs expression that are associated with survival, thus suggesting that SCAMP3 can be used as a clinical diagnosis and prognostic biomarker in HCC.Keywords: SCAMP3, hepatocellular carcinoma, prognosis, interaction, ncRNA, Kaplan–Meier plotter